Outcomes of novel pacing technologies with right ventricular pacing as a primary strategy for patient undergoing transvenous permanent pacing regardless of pacing indication. (14th October 2021) - Abdin, A; Aktaa, S; Vukadinovic, D; Arbelo, E; Boehm, M; Burri, H; Glikson, M; Meyer, C; Munyombwe, T; Nielsen, N C; Vernooy, K; Ukena, C; et al.
Abstract: Background: Right ventricular pacing (RVP) may cause electrical and mechanical desynchrony leading to impaired left ventricular ejection fraction (LVEF). We investigated the outcomes of RVP with His bundle pacing (HBP) and left bundle branch pacing (LBBP) for patients requiring a de novo permeant pacemaker (PPM) irrespective of baseline pacing indication. Methods and results: Systematic review of randomized clinical trials and observational studies comparing HBP or LBP with RVP for de novo PPM implantation between 01 January 2013 and 17 November 2020 using MEDLINE and Embase. Two independent reviewers extracted the data and assessed the risk of bias of included studies. Random and fixed effects meta-analyses of the effect of pacing technology on study outcomes (all-cause mortality, heart failure hospitalization (HFH), left ventricular ejection fraction, QRS duration, lead revision, atrial fibrillation and procedure and pacing metrics) were performed. Overall, 7 studies were included. HBP compared with RVP was associated with decreased mortality (risk ratio [RR] 0.76, 95% CI 0.59 to 0.98), preservation of LVEF (mean difference [MD] 1.2, 95% CI −1.37 to 3.8 vs. −5.22, 95% CI: −6.94 to −3.51), increased procedure duration (MD 15.17 min, 95% CI: 11.27 to 19.07) and more lead revisions (RR 6.30, 95% CI: 2.31 to 17.19). LBBP compared with RVP was associated with shorter paced QRS durations (MD 5.6 ms, 95% CI −6.4 to 17.6) vs. (51.0 ms, 95% CI 39.2 to 62.9) and increased procedure durations (MD 37.78 min, 95% CI: 20.04 to 55.51). Conclusion: Of the limited studies published, this meta-analysis found that HBP and LBBP were superior to RVP in maintaining physiological ventricular activation as an initial pacing strategy. Well conducted comparative studies are required to understand the impact of such novel pacing strategies on clinical outcomes. Funding Acknowledgement: Type of funding sources: None.